2017
DOI: 10.17219/acem/62107
|View full text |Cite
|
Sign up to set email alerts
|

Objectively measured compliance during early orthodontic treatment: Do treatment needs have an impact?

Abstract: Background. Objective assessment of daily wear time of removable appliances is possible, so the next step is to ascertain whether the severity of malocclusion influences patients' compliance. This could help resolve the controversy over the question of whether removable appliance therapy truly works.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 15 publications
2
15
2
2
Order By: Relevance
“…8 Therefore, many researchers focused on establishing factors that would enable us to predict patient cooperation before manufacturing an appliance. [9][10][11][12] Our previous studies, 13 similarly to those by Amado et al, 14 have shown that the degree of compliance depends on the patients' and -more significantly -their caregivers' personality traits.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…8 Therefore, many researchers focused on establishing factors that would enable us to predict patient cooperation before manufacturing an appliance. [9][10][11][12] Our previous studies, 13 similarly to those by Amado et al, 14 have shown that the degree of compliance depends on the patients' and -more significantly -their caregivers' personality traits.…”
Section: Introductionsupporting
confidence: 53%
“…The authors have already made an attempt to objectively assess the effectiveness of some of these criteria in the published studies. 13,25 It is clear that conducting such a study would in the future create evidence-based treatment protocols regarding the DWT.…”
Section: Discussionmentioning
confidence: 99%
“…The result of the present study indicated no signi cant correlation between acceptance of appliance and IOTN-DHC and IOTN-AC. This nding is inconsistent with the results yielded by Sarul et al 14 , who showed signi cant correlation between the severity of malocclusion and compliance and cooperation of orthodontic appliance. It has been veri ed that the more the severe the malocclusion the higher patient's motivation to orthodontic treatment [14,27].The evidences show that the psychological status in patients with severe malocclusion and scores 4 or 5 of IOTN is signi cantly affected by malocclusion [28,29].…”
Section: Discussioncontrasting
confidence: 99%
“…This nding is inconsistent with the results yielded by Sarul et al 14 , who showed signi cant correlation between the severity of malocclusion and compliance and cooperation of orthodontic appliance. It has been veri ed that the more the severe the malocclusion the higher patient's motivation to orthodontic treatment [14,27].The evidences show that the psychological status in patients with severe malocclusion and scores 4 or 5 of IOTN is signi cantly affected by malocclusion [28,29]. The absence of signi cant correlation between acceptance of appliance and severity of malocclusion can be attributed to low to moderate need for orthodontic treatment among our study population (mean of IOTN-DHC= 2.85 ± 0.56).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation